Protocol L - An AFLP approach for assessment of maternal inheritance of gynogenetic sea bass [Pratical guide of protocols: methods of verification of the ploidy] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
In gynogenesis induction, the use of biochemical markers (allozyme) has demonstrated to be a reliable method to confirm maternal inheritance in gynogenetic fish. The AFLP technology is a variation of the DNA fingerprinting technique based on visualization of polymorphic amplified DNA restriction fragments between samples. AFLP technology is robust and reliable and requires only small amounts of DNA, although it requires specific equipment. The objective of this protocol is to demonstrate the potential use of AFLP markers for determining the maternal inheritance of gynogenetic offspring in sea bass.